Teachers’ mental health issues associated with the university reopening at the onset of the post-COVID-19 era in Ecuador - Guamán-Guevara, María Dolores; Teneda, William (Revista Venezolana de Gerencia, 2023)
Progressive return to face-to-face teaching and learning activities were planned to resume worldwide once most higher education community members are vaccinated against COVID-19. However, mental health issues triggered by this imminent return under unprecedented teaching scenarios, mainly among university teachers, may occur. Therefore, this study aims to determine the psychological response of university teachers to the multiple uncertainties generated by the university reopening in Ecuador. A cross-sectional online survey was conducted, and a sample of 273 university teachers completed a semi-structured questionnaire aiming to collect socio-demographic, health conditions, and professional and family-related data. Measures of stress, anxiety, and depression were also collected based on 5-point Smiley Face Likert scales. Data were quantitatively analyzed with multiple linear regression to determine the factors associated with teachers’ mental health outcomes. Stress and anxiety were significantly related to face-face activities scenarios (p<0.001). Factors such as age, marital status, academic degree, pre-infections with COVID-19, family member loss, employment status, and teaching experience were also significantly associated with psychological disorders observed (p<0.05). Findings may help develop timely preventive programs and policies to cope with and mitigate the knock-on effects of future disease outbreaks in Ecuador, consequently helping reduce social and financial costs.